Optimizing university finances: Implementation of performance-based budgeting at UPN “Veteran” Yogyakarta - Sriyono, Sriyono; Saepudin, Asep; Rahmanda, Gita Astyka; Pradessa, Steven Getha (Journal of Business and Information Systems (e-ISSN: 2685-2543), 2024)
Budgeting is essential for organizational success, facilitating effective resource allocation, financial planning, and performance evaluation. Public Service Agencies (BLUs), notably higher education institutions, benefit from financial autonomy that allows flexible fund management to support institutional objectives. This study examines the implementation of Performance-Based Budgeting (PBB) at UPN “Veteran” Yogyakarta through a descriptive research design, focusing on processes, the relationship between budget allocation and institutional performance, and identifying challenges and opportunities. Findings reveal a significant increase in budget realization, rising from 78.2% in 2020 to 96.9% in 2023, positively influencing the attainment of several Key Performance Indicators (IKU). However, measuring budget allocations for individual IKU remains challenging due to overlapping activities that contribute to multiple indicators. This highlights the need for improved budgeting tools and tracking systems to strengthen the connection between expenditures and performance outcomes. The study underscores the importance of refining PBB practices to enhance resource utilization and align institutional performance with strategic goals in higher education